OPTIMIZING TAXPAYER COMPLIANCE THROUGH TAX COUNSELING AND SANCTIONS WITH TAXPAYER AWARENESS AS A MEDIATING VARIABLE (Study Of Individual Taxpayers At KPP Pratama Jakarta Tanah Abang Tiga) - Kiagus Muhammad Amin; Lela Nurlaela Wati; Oktavia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The research aims to examine and analyze the influence of education and tax sanctions on public compliance through public awareness. The study focuses on individuals registered as taxpayers at the Jakarta Tanah Abang Tiga KPP Pratama Office as of January 2024, with a sample size of 382 respondents. The findings reveal the following: Tax education has a positive and significant influence on taxpayer awareness at the KPP Pratama Jakarta Tanah Abang Tiga Office. Tax sanctions have a positive and significant influence on taxpayer awareness at the KPP Pratama Jakarta Tanah Abang Tiga Office. Counseling positively and significantly influences taxpayer compliance at the KPP Pratama Jakarta Tanah Abang Tiga Office. Tax sanctions positively and significantly influence taxpayer compliance at the KPP Pratama Jakarta Tanah Abang Tiga Office. Taxpayer awareness positively and significantly influences taxpayer compliance at the KPP Pratama Jakarta Tanah Abang Tiga Office. Tax education positively and significantly influences taxpayer compliance through taxpayer awareness at the KPP Pratama Jakarta Tanah Abang Tiga Office. Tax sanctions positively and significantly influence taxpayer compliance through taxpayer awareness at the KPP Pratama Jakarta Tanah Abang Tiga Office.